The Dynamics of Hope in Unkrich and Molina’s Coco - Chia-Chi Chien; Ya-huei Wang (k@ta: A Biannual Publication on the Study of Languange and Literature, 2020)
This study analyzes how the characters in Lee Unkrich and Adrian Molina’s animated film Coco, mainly Mamá Imelda, Héctor, and Miguel, manage their emotional responses when they are facing loss, bereavement, or other significant changes in their lives. The study uses Elisabeth Kübler-Ross’s five-stage model of grief to analyze how these characters go through the grieving process. Moreover, in order to suggest how those who are grieving can enter into positive states of mind, the study expands on Kübler-Ross’s original model by incorporating a positive mindset of hope. In dialogue with Unkrich and Molina’s film, the study uses Kübler-Ross’s ideas to explore coping mechanisms that can help manage difficult times in life, while also suggesting the benefits of maintaining a positive mindset through hope.